2003
DOI: 10.1590/s1519-69842003000300008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and relations with site factors in a campos grassland under grazing

Abstract: Spatial distribution patterns and their relations with environmental factors at different scales were identified in ca. 100-ha grassland under cattle and sheep grazing, in Eldorado do Sul, RS, Brazil (30 degrees 05'S, 51 degrees 40'W). The field survey used 138 0.5 x 0.5 m quadrats located systematically on transects along relief gradients. The quadrats were arranged in groups of 3 contiguous quadrats, which were pooled for the analysis, thus forming 46 quadrats 1.5 x 0.5 m, in this way defining two observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In a flat region in the middle of the State, different efforts have found less species when compared to the present study. Focht & Pillar (2003) have found 148 grassland species with vegetation patterns related to relief position and other factors, such as soil moisture, on a study located approximately 35 km west from ours. On the other hand, granitic grassland formations tend to present high species richness, as showed by Boldrini et al (1998) in a study based on point method on Morro da Polícia, where 189 species were surveyed.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In a flat region in the middle of the State, different efforts have found less species when compared to the present study. Focht & Pillar (2003) have found 148 grassland species with vegetation patterns related to relief position and other factors, such as soil moisture, on a study located approximately 35 km west from ours. On the other hand, granitic grassland formations tend to present high species richness, as showed by Boldrini et al (1998) in a study based on point method on Morro da Polícia, where 189 species were surveyed.…”
Section: Discussionmentioning
confidence: 62%
“…Subtropical grasslands, which are also called campos in Brazil (Behling 2002, Focht & Pillar 2003, were dominant in southern Brazilian landscape during late Pleistocene, and its present distribution can be interpreted as a remnant of a drier and cooler climate in the region (Behling 2002, Bredenkamp et al 2002. Thus, campos configure a relict formation, and the knowledge of its floristic and structural features is vital to understand the processes that lead to modern landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Results reported by FOCHT and PILLAR (2003) and by MAIA et al, (2004) showed that the soil seed-bank is related to position in relief, moisture, potassium level, organic material, saturation of base cation exchange, total exchangeable bases and proportion of clay in the soil.…”
Section: Introductionmentioning
confidence: 93%
“…The study of plant communities is essentially comparative and the physiognomy of a vegetation stand is the result of its composition in terms of plant species or types (Focht and Pillar, 2003). The richness and composition of the epiphytic flora is influenced by the phorophyte (Heatwole, 1993;Medeiros et al, 1993;Benzing, 1995;Rudolph et al, 1998;Nieder et al, 1999;Roberts et al, 2005;Fraga et al, 2008), as well as by the vegetation and climate within the forest (Gentry and Dodson, 1987;Nieder et al, 1997).…”
Section: Introductionmentioning
confidence: 99%